The effectiveness of the educational package of happiness skills based on Islamic approach and comparison with Fordyce's happiness package on happiness, life satisfaction and anger control of mothers - Tayebe Vahdani Khorram,; Fatemeh Fayyaz; j avad Eynypour (پژوهشنامه روانشناسی مثبت)
The purpose of the present study was to evaluate of the effectiveness of the educational package of happiness skills based on the Islamic approach for happiness, life satisfaction and anger control in mothers and compared the results with Fordyce package. The research study had two sections, the first section was a package designed according to an Islamic approach and the second step was quantitative with a semi-experimental method with a pre-test, post-test with a comparison group and a two-month follow-up period. The statistical population included married mothers aged 20 to 40 in the whole city of Tehran and the sample were chosen using purposing sampling based on the entry criteria. They were 30 women who were randomly put into two experimental groups and a comparison group. The participants in the experimental group were trained in happiness skills using the Islamic approach in 9 sessions of 90 minutes, and the control group had 8 sessions of 90 minutes. To collect the data, the Fordyce-Isfahan Happiness Questionnaires, Life Satisfaction and Anger Questionnaire were used. Variance analysis with repeated measurements were used for analyzing the data. The findings showed that the happiness skills training package based via the Islamic approach was effective in promoting happiness, life satisfaction and anger control of mothers.IntroductionWomen are the important and basic pillars of every family and play an important role in establishing and maintaining calmness and satisfaction in the family. They are key to identifying and strengthening happiness in the family (Khodadadi & Kalai, 2019). Happiness is a positive emotional state that is characterized by contentment, pleasure, and satisfaction. It includes traits and symptoms such as having positive beliefs about life, positive emotions, and absence of negative emotions (Porfaraj Imran & Rezazade, 2016). The concept of happiness in the Holy Quran is notable. Various studies have been conducted in the field of happiness with an Islamic approach (Mohammadi & Azarbayjani, 2010; Pasandideh, 2011; Zarea et al., 2023; Zarea et al., 2022). Aaccording to Fayyaz and Okhovvat (2018), the meaning of happiness in the Holy Quran is the perception or feeling of openness caused by conquest or receiving blessings that is experienced overtly (on the face) or covertly (internal perception). It causes the mind to expand and it is divided into two false and true types (unstable and stable). Happiness in Quran is associated with a stable state of satisfaction, happiness and expansion (Fayyaz & Okhovvat, 2018). Considering the importance of designing happiness skills training programs based on the Islamic approach in Iran as well as the importance of mothers' happiness in the family, the purpose of this study was to compare the effectiveness of the happiness skills training package with the Islamic approach (as used by Faiyaz and Okhovvat) with the Fordyce happiness training package in regards to factors such as happiness, life satisfaction and anger control of mothers.MethodThe study method was semi-experimental method with pre-test, post-test and 2months follow up. The statistical population of the research included all married mothers aged 20 to 40 in the whole city of Tehran. After the evaluation of the entry criteria, 30 participants were randomly selected and assigned to experimental and comparison groups. The mothers of the experimental group were trained in happiness skills with an Islamic approach in 9 sessions of 90 minutes, and the mothers of the comparison group were trained in Fordyce's happiness program in 8 sessions of 90 minutes. Data was collected using of Fordyce et al.’s (2008) happiness questionnaires, Diener et al.’s (1989) satisfaction with life and Spielberger’s (1999) anger questionnaire. The questionnaires were administered to the participants of both groups in three stages: pre-test, post-test and two-month follow-up. In order to analyze the data, repeated measurement analysis of variance was conducted via SPSS-26. ResultsThe means of the age of the female participants in the Fordyce happiness training group and the Islamic happiness training group respectively were 35.5 (SD = 4.80) and 34.8 (3.88). The results of the independent t-test showed that there was no significant difference between the groups in terms of age. Also, the average length of marriage of the female participants was 15.66 (SD = 4.87) for the Fordyce happiness training group and 11.4 (SD = 4.24) for the Islamic happiness training group. Table 1 shows the results of variance analysis with repeated measurementsTable 1Variance Analysis with Repeated Measurements to Investigate the Change of The Happiness Anger Control, The Life Satisfaction Variable in The Islamic Happiness Education Program Statistical power Effect SizeSig.Fmean of the squaresDegree of freedomSum of squares Effect sourceVariables0.980.490.000116.315725.2031.1444829.499Time  Happiness  0.430.1620.0813.27414.5491.144166.481Time*Group    44.4519.445864.326Error0.0630.0070.7280.12567.626167.626Group    541.355179203.041Error (group)0.9990.55 20.761569.1231.42810.387Time  Anger Control0.4440.147 2.94180.621.42114.808Time*Group    27.41324.207663.578Error0.2750.109 2.077318.3791318.379Group    153.286172605.867Error (group)0.4130.7120.000141.926116.5622233.123Time  Life satisfaction 0.1130.132.171116.562212.071Time*Group    6.0353494.526Error0.1920.0720.2661.3212.781231.598Group    175.351172980.963Time*p< 0/05According to the significant value obtained, the main effect of time has become significant for the variables of happiness, anger, and life satisfaction. In other words, there were significant changes in the mean scores of these variables from the pre-test to the follow-up. In the Islamic happiness group, the mean of the happiness variable changed from 110.9 in the pre-test to 119.1 in the post-test and 124.1 in the follow-up, while the mean of the anger control variable changed from 109.6 in the pre-test to 115.7 in the post-test. and 121.5 in the follow-up. Also, the mean of the life satisfaction variable has changed from 21.7 in the pre-test to 25.6 in the post-test and 27.7 in the follow-up. The level of happiness in the comparison group with the Fordyce package training also increased in the post-test and follow-up, which was less compared to the Islamic happiness package. Fordyce's happiness training package did not reduce the anger control of mothers, but it had a positive effect on the variable of life satisfaction, which was less than the Islamic approach group.ConclusionThe results of the present study showed that the Islamic happiness training program had a significant positive effect on happiness, life satisfaction and anger control in mothers compared to the Fordyce group. Thus, it should be said that the Islamic happiness skills training package was more effective for happiness, satisfaction with life and anger control among mothers than the Fordyce package. It can be argued that using a happiness training packages based on people's culture and beliefs can increase the mental health of Iranian families more efficiently.Ethical ConsiderationCompliance with Ethical Guidelines: We strictly observed all ethical considerations during the research process. It included ensuring the confidentiality of participants' identities and obtaining informed consent from all participants.Author Contributions: This study was written with the participation of all authors. The introduction and method were written by first author. The part of designing the protocol and implementing it was done by first author and second author. All the authors participated in the statistical analysis.Conflict of Interest: The authors declare no conflict of interest for this study.Funding: The authors received no financial support for the study.Acknowledgments: The authors would like to thank all participants for their time and participation in this study.The article is taken from the master's thesis in the field of personality psychology.. Corresponding author